Investigação da ocorrência do vírus chikungunya em gestantes com quadro exantemático em Goiânia-Goiás - Silva, Lucélia Barbosa de Queiróz (2018)
The chikungunya vírus (CHIKV) is an alphavirus transmitted by mosquitoes of the genus Aedes associated with an infection characterized by fever, myalgia, rash and persistent arthralgia. In 2014 with the arrival of the zika virus in Brazil and its association with vertical transmission and consequent microcephaly in newborns, many questions were postulated regarding the transmission of other arboviruses. In this context, several studies point to the perinatal transmission of CHIKV with encephalitis in neonates. In view of these facts, the present study aimed to investigate the occurrence of chikungunya virus in exanthematic pregnant women, in the city of Goiânia, from January 2017 to July 2018. The study population consisted of 70 pregnant women, from which samples were collected which were subjected to the screening of IgM / IgG serological markers using commercial kit, as well as the detection of viral RNA through RT-qPCR. A CHIKV seroprevalence index of 2.8% was identified. Of the pregnant women investigated, a case of positive IgG marker was identified (Case 1) and another showed positive positivity (IgM-IgG-RNA) (Case 2), being described in both cases the symptomatic picture in the first gestational trimester. In these cases, the newborns were positive only for the IgG marker. This is the first study to investigate the occurrence of CHIKV in the state of Goiás, showing a low circulation of CHIKV in our region, especially in the pregnant population. The information obtained reinforces the importance of studies in this population, in order to better understand the profile of this infection in pregnant women, as well as to contribute to the understanding of aspects associated with the pathogeny of this agent.